2017
DOI: 10.1016/j.ecolind.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of urban mobility: Combining life cycle assessment with land-use and transport interaction modelling—Application to Lyon (France)

Abstract: International audienceIn France, greenhouse gas (GHG) emissions from transport have grown steadily since 1950 and transport is now the main source of emissions. Despite technological improvements, urban sprawl increases the environmental stress due to car use. This study evaluates urban mobility through assessments of the transport system and travel habits, by applying life cycle assessment methods to the results of mobility simulations that were produced by a Land Use and Transport Interactions (LUTI) model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…For evaluating the environmental performance of the system, only exhaust direct emissions from the use of vehicles were taken into account. François et al [62] identified nine environmental indicators for the urban transport sector. However, and as shown in [35,61,63], the different stakeholders involved in urban logistics consider mainly global warming and particulate matters.…”
Section: Environmental Impact Estimationmentioning
confidence: 99%
“…For evaluating the environmental performance of the system, only exhaust direct emissions from the use of vehicles were taken into account. François et al [62] identified nine environmental indicators for the urban transport sector. However, and as shown in [35,61,63], the different stakeholders involved in urban logistics consider mainly global warming and particulate matters.…”
Section: Environmental Impact Estimationmentioning
confidence: 99%
“…refs. [23][24][25][26][27][28][29][30][31][32] ). However, these assessments are often limited in that they (i) have a limited impact coverage (typically centered on climate change and energy demand), [24][25][26][27] (ii) have a narrow technological scope that covers only a few EV technologies (often only hybrid and battery electric vehicles), 23,25,28 (iii) do not embrace an all-inclusive fleetbased perspective, thus leaving out parts of the system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…charging infrastructures), [29][30][31] or (iv) do not encompass a future-oriented perspective. 32 To the knowledge of the authors, no studies have addressed all 4 limitations and investigated a large panel of technologies in a complete, foresight fleet-based assessment with a large impact coverage. 16,17,33 In the context of urban transport planning, such limitations undermine the reliability and relevance of the assessment results and the subsequent support provided to decision-makers.…”
Section: Introductionmentioning
confidence: 99%
“…Además, la calidad del agua es consecuencia de fenómenos naturales y el actuar del ser humano, además es una función de uso del suelo en elárea de captación. Hoy en día se reconoce que la forma en que los seres humanos utilizan y ocupan la tierra tiene una implicación directa en la calidad del agua y, por lo tanto, se preconiza que el control de calidad del agua se asocia con una planificación global a nivel deárea de captación entera y no de forma individual para cada fuente que recibe un impacto directo [10], [11].…”
Section: Introductionunclassified